2018
DOI: 10.1111/jen.12496
|View full text |Cite
|
Sign up to set email alerts
|

Development of Asian parasitoids in larvae Of Drosophila Suzukii feeding on blueberry and artificial diet

Abstract: In just a few years, the Asian fly Drosophila suzukii has invaded several continents and has become a very serious pest of many fruit crops worldwide. Current control methods rely on chemical insecticides or expensive and labour-intensive cultural practices. Classical biological control through the introduction of Asian parasitoids that have co-evolved with the pest may provide a sustainable solution on condition that they are sufficiently specific to avoid non-target effects on local biodiversity. Here, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 46 publications
1
24
1
Order By: Relevance
“…Previous investigations on D . suzukii— parasitoids interactions were obtained mainly by quantifying the final outcome (numbers of emerged non-parasitized adult flies, adult flies with capsules or parasitoids [ 23 25 , 27 29 ]), without monitoring in details the physiological interactions. Here, we sought to better understand the success or failure of parasitism of sympatric and allopatric endoparasitoid wasps on the larval stages of D .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations on D . suzukii— parasitoids interactions were obtained mainly by quantifying the final outcome (numbers of emerged non-parasitized adult flies, adult flies with capsules or parasitoids [ 23 25 , 27 29 ]), without monitoring in details the physiological interactions. Here, we sought to better understand the success or failure of parasitism of sympatric and allopatric endoparasitoid wasps on the larval stages of D .…”
Section: Discussionmentioning
confidence: 99%
“…heterotoma kills about 40% of D . suzukii larvae and is successful at a low rate in laboratory, which probably accounts for the undetected emergence of this parasitoid from field exposed larvae or sampled pupae in fruits [ 19 , 25 , 64 , 65 ]. In semi-natural conditions, we observed that L .…”
Section: Discussionmentioning
confidence: 99%
“…In experiment A, A. japonica, L. japonica and L. heterotoma were tested on D. suzukii , D. melanogaster , D. immigrans , D. subobscura and D. busckii in plain regular CAROLINA© diet instead of fruit (Table 1, Experiment A), because Girod et al (2018a) demonstrated that these species would show the same parasitism behaviour with larvae in this artificial diet and blueberries. In experiment B, the two populations of Ganaspis cf.…”
Section: Methodsmentioning
confidence: 99%
“…is not accepted as substrate by Ganaspis cf. brasiliensis (Girod et al 2018a ). However, besides D. suzukii, none of the Drosophila species used in this study lays eggs in fresh fruits.…”
Section: Methodsmentioning
confidence: 99%
“…The parasitoids Asobara japonica, Leptopilina japonica, and Ganaspis cf. brasiliensis may be good candidates [142][143][144]. For this option, however, various regulations need to be met with, including the Nagoya protocol and phytosanitary regulations for import and release of biocontrol agents to avoid unwanted effects on non-target organisms [145][146][147].…”
Section: Additional Density Reduction Methodsmentioning
confidence: 99%